Rapid expansion of pastures in Northern Lao PDR revealed by geospatial analysis - Himel, Jeffrey; Jalonen, Riina; Kong-Ay, Khampaseuth; Vongkhamho, Simone; Bountihiphonh, Chaloun; Xaypheng, Nout; Chanhthavong, Somsack; Notenbaert, An; Muthoni, Francis (2024)
In response to growing livestock demand from China and Vietnam, labour shortages and increasingly adverse weather, many farmers in Northern Lao PDR are transitioning from annual cropping to cattle rearing. While livestock expansion has economic benefits, it poses significant environmental risks. Pasture expansion has contributed to deforestation, increased greenhouse gas emissions, land degradation, loss of ecosystem services and reduced climate resilience. Sustainable intensification of livestock production systems in the region is essential to improve productivity, optimize resource use, and enhance socio-ecological resilience amid volatile global markets, land degradation, and environmental change. The objective of this study was to apply remote sensing and field inventory data analyze land use/land cover changes (LULCC) in three districts in Luang Prabang and Xieng Khouang provinces of Lao PDR, with a special focus on conversions to and from pasture lands. Specific research questions were: (1) What is the extent of land cover change towards pasturelands from 1993 to 2023? (2) How much of the pasturelands are in areas with elevated environmental risks, and would thus particularly benefit from sustainable intensification such as silvopasture? The results revealed a rapid land use change towards pasturelands, especially since 2010, with pasture expansion reaching almost 700% in Phonxay district (Luang Prabang) and 400% in Mok and Nonghet districts (Xieng Khouang), compared to the 1993 baseline.